Estufa para o cultivo de vegetais e seus fundamentos físicos - Pimenta, Robson David (2022)
Diversify the techniques and methodologies in the classroom becomes increasingly forceful and necessary. Through this work, the most attractive and instigating physics classes in the third year of high school at the Lindolfo Mendes da Cunha State College, Faina-GO, was sought through this work. In the implementation of these classes, the construction of a wooden greenhouse of LED lamps of various colors was used to verify their influences on plant growth. Some concepts such as luminous radiation intensity, temperature, humidity, absorption and reflection of light, emission of black body radiation, their greenhouse relations were treated in classes. It was also sought to manage the classes in an interdisciplinary way involving biology and physics in photosynthesis and greenhouse effects. The classes were very dynamic and productive according to student report. Bringing the physical, chemical and biological phenomena of everyday life to be debated and studying in the classroom brought meaningful learning to light. Thus, the experimentation and current themes worked in the classroom demonstrated greater engagement from the students facilitating learning and even the indiscipline that are often narrated by teachers.